PENGENDALIAN SUHU DENGAN METODE PID PADA ALAT PENETAS TELUR - Zacky Yarfa'ul Ahla; Akhmad Musafa (MAESTRO, 2019)
Control becomes important as a deciding success in a process. One of which is a system that controls the temperature of the egg hatch using a mega Arduino 2560. The purpose of this system is to reduce failure during hatching of chicken eggs. At this final task will be discussed about temperature control by using the PID on the egg hatch tool. In the design of the tool this time using the LCD 20 x 4, sensor DHT2, Driver motor IBT-2, PTC Ceramic Air Heater with a power of 170 watts and a 12-volt, Fan 12 VDC with a size 12 cm x 12 cm. Component PTC Ceramic Air Heater and DC fan will be assembled into a A range of controls using the PID algorithm with a programming language using the language C. The automation done is by measuring the temperature in the egg hatching room with a setpoint value of 36 ° C-39 ° C. Temperature measurements are carried out using the DHT22 sensor, then tunning the PID with a heuristic method so that the overall test is obtained by the result of a comparison system response between normal temperature and AIR conditioned room temperature. The process Indicates the performance of the system works well in accordance with the value of the temperature that can be maintained at SetPoint, where the temperature value is estimated to hatch eggs. Keywords: Arduino Mega 2560, LCD 20 x 4, DHT22, PTC Ceramic Air Heater, Fan DC, Motor Driver IBT-2, PID.